Molecular Mechanisms Generating and Stabilizing Terminal 22q13 Deletions in 44 Subjects with Phelan/McDermid Syndrome - Bonaglia, Maria Clara; Giorda, Roberto; Beri, Silvana; De Agostini, Cristina; Novara, Francesca; Fichera, Marco; Grillo, Lucia; Galesi, Ornella; Vetro, Annalisa; Ciccone, Roberto; Bonati, Maria Teresa; Giglio, Sabrina; et al. (PLoS genetics, 2011)
In this study, we used deletions at 22q13, which represent a substantial source of human pathology (Phelan/McDermid syndrome), as a model for investigating the molecular mechanisms of terminal deletions that are currently poorly understood. We characterized at the molecular level the genomic rearrangement in 44 unrelated patients with 22q13 monosomy resulting from simple terminal deletions (72%), ring chromosomes (14%), and unbalanced translocations (7%). We also discovered interstitial deletions between 17-74 kb in 9% of the patients. Haploinsufficiency of the SHANK3 gene, confirmed in all rearrangements, is very likely the cause of the major neurological features associated with PMS. SHANK3 mutations can also result in language and/or social interaction disabilities. We determined the breakpoint junctions in 29 cases, providing a realistic snapshot of the variety of mechanisms driving non-recurrent deletion and repair at chromosome ends. De novo telomere synthesis and telomere capture are used to repair terminal deletions; non-homologous end-joining or microhomology-mediated break-induced replication is probably involved in ring 22 formation and translocations; non-homologous end-joining and fork stalling and template switching prevail in cases with interstitial 22q13.3. For the first time, we also demonstrated that distinct stabilizing events of the same terminal deletion can occur in different early embryonic cells, proving that terminal deletions can be repaired by multistep healing events and supporting the recent hypothesis that rare pathogenic germline rearrangements may have mitotic origin. Finally, the progressive clinical deterioration observed throughout the longitudinal medical history of three subjects over forty years supports the hypothesis of a role for SHANK3 haploinsufficiency in neurological deterioration, in addition to its involvement in the neurobehavioral phenotype of PMS.